2020
DOI: 10.1002/adtp.202000018
|View full text |Cite
|
Sign up to set email alerts
|

ImmunoPET Imaging of TIM‐3 in Murine Melanoma Models

Abstract: T cell immunoglobulin and mucin domain-containing-3 (TIM-3) is an immune checkpoint expressed mainly on CD4 + and CD8 + T cells. In addition to negatively regulating inflammatory T cell function, TIM-3 is a promising immunotherapy target. Herein, the aim is to develop an immuno-positron emission tomography (immunoPET) probe for noninvasively characterizing TIM-3 expression. Flow cytometry is used to detect the expression levels of TIM-3 in B16F10 cells. RMT3-23, a rat antimouse TIM-3-specific monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…Some common obstacles to the wide implementation of immunoPET include the high costs, advanced technology to commercially produce pure mAbs, difficulties in conjugation and in vivo tracer stability, as well as high circulation time and physiologic uptake after administration. Recent developments are answering these needs ( 97 , 411 ) and will continue to evolve. Although immunoPET can become a diagnostic tool in specific conditions, its primary role seems to be a complementary imaging tool for therapy guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some common obstacles to the wide implementation of immunoPET include the high costs, advanced technology to commercially produce pure mAbs, difficulties in conjugation and in vivo tracer stability, as well as high circulation time and physiologic uptake after administration. Recent developments are answering these needs ( 97 , 411 ) and will continue to evolve. Although immunoPET can become a diagnostic tool in specific conditions, its primary role seems to be a complementary imaging tool for therapy guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, radiotherapy-induced PD-L1 upregulation was demonstrated in melanoma mouse models, using radiolabeled anti-PD-L1 Abs ( 348 , 349 ). Another immune checkpoint, T-cell immunoglobulin and mucin domain-containing-3 (TIM-3), was a successful target for murine melanoma models ( 97 ). One clinical study evaluated [ 89 Zr]Zr-pembrolizumab in melanoma, reporting relations between tracer uptake and response to therapy and survival in patients with advanced or metastatic disease ( 347 ).…”
Section: Immunopet In Different Malignanciesmentioning
confidence: 99%
“…[ 89 Zr]Zr-TIGITmAb detected TIGIT+tumor infiltrating lymphocytes in a melanoma allograft mouse model. 32 T cell immunoglobulin and mucin domain-containing-3 (TIM-3) is another immune checkpoint for which a PET tracer was developed, 33 namely a rat anti-mouse TIM-3specific monoclonal antibody [ 64 Cu]Cu-NOTA-RMT3-23.…”
Section: Other Immune Checkpointsmentioning
confidence: 99%
“…To our knowledge, only one study has been performed with a TIM-3 targeting tracer. Wei et al (2020) have developed 64 Cu-NOTA-RMT3-23 to visualize TIM-3 expression in murine models [43]. Their study showed the presence on TIM-3 positive cells on the edge of the tumors as well as high uptake in the liver and spleen.…”
Section: Tracer Features/validation Statementioning
confidence: 99%